FAO fisheries technical paper N359: Chronicles of marine fishery landings ( 1950 - 1994 ): Trend analysis and fisheries potential - R J R. Grainger (FAO, 1996)
Through a preliminary analysis of trends, globally and by oceans, the authors attempt to demonstrate that these extended time series can be very useful in interpreting developments in the world's fisheries and so help in assessing the present situation as well as for planning and policy-making for the future. Grouping the 200 most important resources into a few categories according to the shapes of their landings trends, reveals a variety of patterns which seem to form different segments of a generalised fishery development model comprising undeveloped, developing, mature and senescent phases. The analysis demonstrates strikingly the sucession of the passage of the majority of the world's major resources through these phases, indicating the current general saturation of fisheries development and increasing overexploitation.